Pembelajaran Terintegrasi Budaya Lokal Melalui Tradisi Maccera Siwanua - Hasriyanti, Hasriyanti (LaGeografia, 2021)
Indonesia as a multicultural nation rich in various local wisdom, becomes the basis of the importance of local cultural integarasi in education in building the culture of life. This study presents a finding of creative learning potential through understanding the value contained as a form of cultural wealth in Alitta Village, Mattiro Bulu Subdistrict, Pinrang Regency. This study uses an ethnographic approach, which aims to explain and describe how the process and cultural values contained related to Maccera Siwanua. Alitta indigenous peoples are a group of people who have ancestral origins (hereditary) in a certain geographic region and have their own system of values, ideology, economy, politics, culture, social and region. This tradition is one of the products of local culture passed down through generations by ancestors who still exist and survive until the current era of globalization, in addition, cultural values are attached simultaneously at every stage of the ritual. Speech and deeds of leaders and ritual societies become the main focus to uncover these cultural values. Maccera Siwanua ritual in Alitta society, produces cultural values that can at least be used as a reference in pedidikan and living a better daily life, such as piety to The One True God, mutual respect, innate good heart, unity, and deliberation.